Ethnomathematical Exploration of Bamboo Weaving Crafts in Geometry Learning in Sukabumi Regency - Astuti, Asti Fuji; Yusup, Rinaldi (Jurnal Kiprah Pendidikan, 2025)
Mathematics is frequently perceived as an abstract discipline, disconnected from everyday life, thus necessitating the implementation of contextual learning approaches. Ethnomathematics is one such approach that connects mathematical concepts with local culture. This study aims to explore the ethnomathematical values found in bamboo weaving crafts in Sukabumi Regency and their relevance to geometry learning in schools. This study employed a qualitative approach through ethnographic methods. Data were collected through literature studies, observation, in-depth interviews, and documentation involving traditional bamboo weaving artisans. The sample was selected using purposive sampling, focusing on artisans who are actively involved and understand the traditional weaving process. The data were analyzed using thematic analysis to identify geometric patterns found in the woven motifs. The findings reveal the presence of various geometric forms such as cuboids, triangles, squares, and symmetrical patterns within the bamboo weaving crafts. These findings indicate that traditional crafts can serve as contextual learning media that strengthen students' understanding of geometric concepts while also instilling local cultural values. The implications of this study suggest that the exploration of ethnomathematics in bamboo weaving crafts can serve as a foundation for developing contextual and culturally based geometry learning materials and modules. Furthermore, integrating local culture into learning is believed to enhance student engagement and enrich more meaningful learning experiences.